A RESEARCH PAPER ON MONETARY POLICY AND INFRASTRUCTURAL GROWTH: FURTHER EVIDENCE FROM NIGERIA. - Igbinedion, Sunday Osahon (Advances in Social Sciences Research Journal, 2020)
Extant economic literature has acknowledged monetary policy as a key factor influencing infrastructural growth through different channels, such as affordable housing and efficient transportation, among others. However, in recent times, the Nigeria’s experience suggests a conflicting position on the above supposition. It is against this backdrop that this study set out to investigate the nexus between monetary policy and infrastructural growth within the Nigerian context, time series data from 1981 to 2018, and utilizing the Fully Modified Least Squares (FMOLS) estimation technique. The results show that both real interest rate and inflation rate exerted negative and statistically significant impact on infrastructural growth, while federal government capital expenditure and net official development assistance impacted positively on the level of infrastructural growth in the period under assessment. In the light of the study’s findings, the study recommends that, the monetary authority should carefully review existing lending interest rate downward to a single digit that will be investment driven particularly in the face of current global economic uncertainties occasioned by the COVID-19 pandemic that has led to the collapse of many economies across the world.